Attitude of Nursing Students of Nepal towards Online Learning - Gurung , Nirsuba; Gaire, Bipula; Dhungana , Govinda Prasad (Journal of Karnali Academy of Health Sciences, 2021)
ABSTRACT Introduction: Technology has influenced almost every aspect of life, and education is no exception. Digitization in education has made it more convenient and flexible. Likewise in present situation caused by COVID-19 pandemic, online education is an option to continue teaching-learning activities. Many nursing colleges of Nepal have started online classes. This study aims to assess the attitude of nursing students of Nepal towards online learning; as learner’s attitude is one of the critical factors for meeting the learning objectives. Methodology: A quantitative web-based cross-sectional study was conducted among 423 Nepalese nursing students. Data collection was done online through a structured, self-administered, pre-tested questionnaire consisting of socio- demographic and academic questions and 5-point Likert scale to assess the attitude of the students. Data were analyzed in SPSS 16 using descriptive and inferential statistics. Result: Total 423 students were enrolled in the study. The mean age of the students was 22.22 years. One-third of the students were from Kathmandu University-affiliated colleges and half of them were studying B. Sc. Nursing. Sixty nine percent of them owned both mobile and laptop whereas 1/3rd of them had weak Wi-Fi connections. Fifty two percent had positive attitude towards online learning, which was significantly associated with age (2=8.37, p-value 0.039), university affiliation (2=5.23, p-value 0.022), course of study (2=14.03, p-value 0.001), and strength of internet connection (2=25.97, p-value<0.001). Conclusion: Only half of the students were having a positive attitude towards online learning, which is not sufficient for effective results.